Are Sportive Games Affecting the Lipid Profile in Adolescents? - Vedat Çınar; Taner Akbulut; Yakup Kılıç; Zarife Pancar (Türk Spor ve Egzersiz Dergisi)
The purpose of this study was to investigate the effects of sportive games on the lipid profile in some selected branches for ten weeks applied to adolescents.